Making sense of Philippine egovernment services through the egovernment services quality model and public value perspective a case study on the DFA Passport Application System - Fabian, Mary Nicole Tejero 1996-; Lapada, Ronna Chris Letigar (2018)
"The success of an eGovernment service in a country is dependent on the value that the citizens attribute to it and the quality of service that it provides. In this case study, the researchers measured the success of the Department of Foreign Affairs Passport Application System through the Public Value perspective (Moore, 1995) and the eGovernment Services Quality Model (Fan & Yang, 2015). Using a mixed method approach of an online survey and one-on-one interviews, the researchers inferred the connection between the evaluation of user satisfaction and in measuring the performance of public services of the DFA Passport Application System which are both citizen-centric in focus and perspective. Overall, results showed that the relationship between all variables were all significant and had a positive correlation to each other. Conclusively, findings show that the overall eGovernment Services Quality and Public Value of the DFA Passport Appointment System falls only under the positive neutral ranking. This may be supported by the fact that based from the qualitative findings, there are still a lot of improvements that could and should be done on the DFA Passport Application System in order to create a much better passport application and renewal experience for Filipino citizens."